Phantom waltz eaudiobook Kendrick/coulter/harrigan series, book 2. - Anderson, Catherine (Kendrick/Coulter, 2002)
Catherine Anderson has won nine consecutive KISS Awards for her books including Baby Love and Cherish. A New York Times best-selling author, she never fails to create characters that capture readers' hearts. Phantom Waltz is a story of love and of victory over great obstacles. The first time wealthy rancher Ryan Kendrick sees Bethany Coulter, he falls in love. She shares his passion for horses and can light up a room with her smile. She is perfect in every way—except a riding accident years ago has confined her to a wheelchair. Bethany is convinced that she will never marry or bear children. Now Ryan wants to change her mind. As Ryan tries to win Bethany's trust and her heart, he must use all his resources to learn how to care for her. Phantom Waltz is a truly heartwarming work that portrays both physical challenges and emotional triumphs.